Pengaruh Budaya Organisasi dan Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru Melalui Motivasi Kerja Sebagai Variabel Mediasi di SMA N 2 - Widyanti Putri; M. Afuan; Desi Purnama Sari (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study investigates the influence of organizational culture and school leadership on teacher performance through work motivation as an intervening variable at SMA N 2 Pasaman Barat. The research employed a quantitative approach, with the entire population consisting of 46 teachers serving as respondents. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method, including assessments of both the outer and inner models, as well as hypothesis testing. Data processing was conducted with the SmartPLS 3 software package to ensure accuracy and reliability in statistical analysis. The findings reveal that organizational culture has a significant positive effect on work motivation, indicating that a supportive and constructive organizational environment fosters higher levels of teacher motivation. Similarly, school leadership demonstrates a substantial impact on work motivation, emphasizing the importance of principals in inspiring and guiding teachers to remain engaged in their professional roles. Furthermore, the analysis shows that organizational culture significantly affects teacher performance, suggesting that strong cultural values and shared norms within the school enhance overall effectiveness in teaching. In contrast, the results indicate that school leadership does not have a direct significant effect on teacher performance, highlighting that leadership influence may be indirect, primarily channeled through motivational factors. Additionally, work motivation itself is found not to exert a substantial effect on teacher performance, suggesting that motivation alone may be insufficient without being supported by other organizational and contextual factors. When tested as an intervening variable, work motivation does not significantly mediate the relationship between organizational culture and teacher performance, nor between school leadership and teacher performance. Overall, the study contributes to the understanding of how organizational culture and leadership interact with teacher motivation and performance, with implications for educational management strategies aimed at enhancing teacher outcomes in secondary schools.